(untitled) (The International Journal of Educational Sciences and Arts, 2025)
Iraq has recently witnessed a series of social changes that have resulted in several negative phenomena in Iraqi society, especially among young people. The most prominent of these is the spread of drug abuse and the resulting risks that threaten the safety of its members, impact their physical, psychological, and mental energies, and hinder their ability to work. Studies and research have confirmed that drug abuse is more prevalent among young people. Hence, the role of educational institutions in caring for them and protecting them from its serious effects on the individual and society, in order to limit its use and spread. The problem of drug abuse is constantly on the rise. Therefore, it has become imperative for all institutions, especially educational institutions, to play an effective role in reducing this phenomenon. This prompted the researcher to develop a proposed vision for the role of educational institutions in reducing the phenomenon of drug abuse among young people in Iraq after 2003, with the aim of preventing drug abuse. The research is divided into three chapters. The first chapter (introduction to the research) includes the research problem, the importance of the research, the research objectives, and research terminology. The second chapter (theoretical aspects) includes a historical overview of drugs, the causes that lead to addiction, types of drugs, theories explaining drugs, and methods of drug use. Chapter Three includes a proposed vision for the role of educational institutions in reducing drug abuse among youth. It covers the objectives of the vision and the roles of the family, school, and media in reducing youth drug abuse.